Successful Use of Human AB Serum to Support the Expansion of Adipose Tissue-Derived Mesenchymal Stem/Stromal Cell in a Microcarrier-Based Platform - Moreira, Francisco; Mizukami, Amanda; de Souza, Lucas Eduardo Botelho; Cabral, Joaquim M. S.; da Silva, Cláudia L.; Covas, Dimas T.; Swiech, Kamilla (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem/stromal cells (MSC) are promising candidates for cell-based therapies and for the promotion of tissue repair, hence the increase of clinical trials in a worldwide scale. In particular, adipose tissue-derived stem/stromal cells (AT MSC) present easy accessibility and a rather straightforward process of isolation, providing a clear advantage over other sources. The high demand of cell doses (millions of cells/kg), needed for infusion in clinical settings, requires a scalable and efficient manufacturing of AT MSC under xenogeneic(xeno)-free culture conditions. Here we describe the successful use of human AB serum (10%(v/v)) as a culture supplement, as well as coating substrate for the expansion of these cells in microcarriers using (i) a spinner flask and (ii) a 500-mL mini-bioreactor (ApplikonTM Biotechnology). Cells were characterized by immunophenotype and multilineage differentiation potential. Upon an initial cell adhesion in the spinner flask of 35 ± 2.5%, culture reached a maximal cell density of 2.6 ± 0.1 x 105 cells/mL at day 7, obtaining a 15 ± 1-fold increase. The implementation of the culture in the 500-mL mini-bioreactor presented an initial cell adhesion of 22 ± 5%, but it reached maximal cell density of 2.7 ± 0.4 x 105 cells/mL at day 7, obtaining a 27 ± 8-fold increase. Importantly, in both stirred systems, cells retained their immunophenotype and multilineage differentiation potential (osteo-, chondro- and adipogenic lineages). Overall, the scalability of this microcarrier-based system presented herein is of major importance for the purpose of achieving clinically meaningful cell numbers.